The effectiveness of structured respiratory physiotherapy protocol on lung function in sugarcane industrial workers - Patil Poonam; Patil, Chandrakant (International Journal of Psychosocial Rehabilitation, 2020)
Background:there is significantly increased risk of respiratory morbidity and mortality among industrial workers. In this locality baggasis is most common condition as there are sugarcane industries. Hence there is need to find the effect of structured respiratory protocol on sugarcane industrial workers. There is limited study done in sugarcane industries. Repeated exposure to dusty environment in an industry causes airway diseases which may affect pulmonary function over a period of time. Materials and methodology: -60 workers of age group 25-45 from sugar industry participated in this study. The subjects were scrutinized based on the inclusion criteria. All the subjects signed a consent form prior to participation in the study. Before receiving any intervention, the peak expiratory flow rate and the pulmonary function (FVC, FEV1, FEV1/FVC %, FEF25-75%) was recorded by a computerized spirometer, and 6min walk test was taken. After recording the pre-intervention outcome measures, a structured exercise protocol for 3 months was given to the subjects followed by post intervention recording of the outcome measures. After the procedure statistical analysis was done using the paired t test.Result:In this study pre-intervention peak expiratory flow rate was 290±58.251 and post-intervention peak expiratory flow rate was 307±60.914. In peak expiratory flow rate statistically extremely significant difference and increasing peak expiratory rate post intervention with (p<0.0001) with t=5.633 with 59 degree of freedom. The forced vital capacity (FVC) increased from 44% to 71% of predicted but there was no change in forced expiratory volume in the first second (FEV1). The six-minute walk distance (6MWD) increased from 215 to 297 meter.Conclusion:-thus, the above study concluded that a structured exercise programme showed a significant improvement clinically as well as statistically on the peak expiratory flow rate , the pulmonary function and 6 minute walk test in the sugar industry workers. Hence it accepts the alternate hypothesis.